Investigation of mitigation and detection methods of Open Phase Conditions (OPCs) in nuclear power plants based on the operating experience - Bass, Cindy Allison (Department of Electrical Engineering, 2019)
Safety in a Nuclear Power Plant (NPP) is of utmost importance, as the implications of a nuclear event have dire consequences on people, animals, and the environment and on unborn generations. This dissertation is about Open Phase Conditions (OPCs), which occur when one or two of the three electrical phases are lost or open circuited, e.g. one circuit breaker phase doesn’t open or close. The study of this condition is important, as it can affect important-to-safety equipment, which is critical to the safe shutdown systems of the reactor in a nuclear power plant. The OPC can occur in the transmission (TX) switchyard or at the transformers connected to the nuclear plant. It also has the capability to make the offsite supply inoperable, which is the alternate source of power for the nuclear safety systems. As many as sixteen (16) cases of Open Phase events have occurred in different countries worldwide from 1994 till 2015. An event also occurred in the Koeberg Nuclear Power Station (KNPS) in South Africa on the 11th November 2005. When these events occurred, the protection schemes did not “see” nor isolate the condition, as this was discovered to be a design vulnerability. This was due to oversight in the design of the protection to detect this condition. This dissertation seeks to answer the following research question: Is it possible to prevent or mitigate an open phase condition from occurring in the switchyard of a nuclear power plant? Previous work has attempted to address the lack of awareness of people working in close proximity to a Nuclear power station i.e. amongst staff working in the switchyard and operators in a nuclear plant, by sharing the operating experience (OE) of OPC occurrences. The approach to answer the research question lies in the analysis of the awareness of the people involved, as the condition cannot be prevented if it is not known. Case studies of the documented OE were categorised and analysed using a simplified root cause analysis method. A survey was conducted to assess the OPC awareness and perceptions of people in the system operator, i.e. TX division and at the Koeberg nuclear power station, within the Eskom Holdings utility. The results demonstrate that there is insufficient overall knowledge and understanding of this condition within the system operator. Operators in the nuclear plants all over the world have been required by the US Nuclear regulator, to be trained and to be aware of this condition. The results of this dissertation highlight the focus areas in people’s awareness that need attention. And that educating the system operator through training will strengthen the relationship between transmission and the nuclear plant within Eskom holdings.